THE RELATIONSHIP BETWEEN INTENSITY OF PLAYING ONLINE GAMES AND AGGRESSIVE BEHAVIOR IN UPPER GRADE ELEMENTARY SCHOOL STUDENTS - Widyadhari, Ailsa Athalia; Dwi, Nastiti (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The increasing phenomenon of aggressive behavior among students in schools has become a critical issue that requires serious attention. Currently, aggressive behavior is not only found among middle and high school students but also among elementary school students. An initial survey revealed that several students exhibited aggressive behaviors such as hitting, pushing, throwing objects, mocking, threatening, and using harsh language. This study aims to examine the relationship between online gaming and aggressive behavior among upper-grade elementary school students at SDN Tanggul. Method: The research employs a quantitative approach with a correlational research design. The sampling technique used is total sampling, involving 135 students.  Results:  The correlation test results indicate a score of (r = 0.762, p-value < 0.001), which suggests a significant positive relationship between the intensity of online gaming and students' aggressive behavior. The findings reveal that the majority of students have a moderate level of online gaming intensity (57%) and exhibit moderate levels of aggressive behavior (67.4%). Novelty:  The uniqueness of this study lies in its focus on the research subject. Unlike previous research, which examined the relationship beetween online gaming and aggressive behavior among vocational high school student, this study specificially investigates the instensity of online gaming and its correlation with aggressive behavior among upper-grade elementary school students.